PERSONNEL DEVELOPMENT OF GREEN HOTEL UNDER CARBON NEUTRALITY IN SAMUI ISLAND AND PHUKET - Phoochinda, Wisakha; Vongchan, Paron (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
This study aims to investigate the demand for developing the potential of green hotel personnel under carbon-neutral tourism and to develop curriculum for improving the potential of green hotel personnel based on the carbon-neutral tourism in Samui Island and Phuket. Data was collected from questionnaires of 410 hotel personnel in Samui Island and Phuket on the general information, as well as information on green hotel business services activities, e.g., environmentally friendly procurement, environmental and energy management, and local and community participation. And then, quantitative data was used to develop a curriculum for green hotel personnel under a carbon-neutral tourism. The study found that most of the personnel are operational and work at a room department. The demand or expectation for developing the potential of green hotel business under carbon-neutral tourism involves the mechanism for developing environmental friendly tourist attractions in the area. The contents that most of the sample groups needed to develop their potential include environmental management and sustainable energy in green hotels in which convenient channel for receiving training is online training. The curriculum structure for green hotel towards carbon-neutral tourism is divided into five issues: Environmental Friendly Service Policy, Human Resource Development, Public Relations Activities, Environmental Friendly Procurement, and Environmental and Energy Management. The curriculum emphasizes on resource management, services and safety for tourists, environmental responsibility, energy saving, as well as local awareness on social, cultural and economic aspects. The hotel staff could, therefore, apply this knowledge to manage good services with environmental concerns in their hotels and communities.